(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The movement of fluid between coaxial cylinders is considered in two cases: The inner cylinder moves at a constant speed that occur under the influence of pressure conditions; a relationship is obtained for the ratio of the radii, provided that the cylinder speed in the first case is equal and the average fluid velocity in the second